Study on Monitoring Rock Burst through Drill Pipe Torque - Zhonghua Li; Liyuan Zhu; Wanlei Yin; Yanfang Song (Shock and Vibration)
This paper presents a new method to identify the danger of rock burst from the response of drill pipe torque during drilling process to overcome many defects of the conventional volume of drilled coal rubble method. It is based on the relationship of rock burst with coal stress and coal strength. Through theoretic analysis, the change mechanism of drill pipe torque and the relationship of drill pipe torque with coal stress, coal strength, and drilling speed are investigated. In light of the analysis, a new device for testing drill pipe torque is developed and a series of experiments is performed under different conditions; the results show that drill pipe torque linearly increases with the increase of coal stress and coal strength; the faster the drilling speed, the larger the drill pipe torque, and vice versa. When monitoring rock burst by drill pipe torque method, the index of rock burst is regarded as a function in which coal stress index and coal strength index are principal variables. The results are important for the forecast of rock burst in coal mine.